Mini-Crack Detection of Conveyor Belt Based on Laser Excited Thermography - Fei Zeng (MDPI AG, 2021)
For a belt conveyor, a belt with mini-cracks influences the safety of the operation of the belt conveyor devices significantly. The lumpy material rubbing against a belt with mini-cracks will lead to detrimental tears on the belt while the conveyor works at high speeds. In order to detect mini-cracks in a timely manner, before the occurrence of large tears, a new mini-crack detection method for conveyor belts based on laser excited thermography is proposed. A laser beam is applied to generate a heat wave on the belt surface, so the corresponding thermal images can be recorded by an infrared camera. Then, an algorithm for extracting and fusing the features of mini-crack belt’s thermal images is firstly proposed by using time sequence analysis. It could transform multiple sequential thermal images into a single thermal image according to the frame difference method, so that the infrared thermal response of the mini-crack over time could be recorded quickly. To reveal the features of mini-crack, the power function image enhancement algorithm is proposed. After that, the threshold segmentation and Hough transform algorithm are used to determine the size of the mini-crack. The experimental results show that the mini-cracks with length of 50–140 mm, width of 1–10 mm, and depth of 5 mm can be successfully detected, and the detection accuracy could reach 96%. The detection results of different sizes of mini-crack show that the laser excited thermography has high damage sensitivity (1 mm diameter mini-crack detection), high accuracy (96%), lower power consumption (15 W laser excitation), and high SNR (signal-to-noise ratio).